2011
DOI: 10.4103/0019-5545.91911
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental health in pregnancy and child behavior

Abstract: Maternal mental health research is a public health priority due to its impact on both maternal and child health. Despite the growing number of empirical studies in this area, particularly from developing countries, there is a paucity of synthetic review articles. Therefore, attempting to synthesize the existing literature in this area seems relevant to appraise the readers of the field's progress and to infer directions for future research. The present review aims to provide an overview of the literature on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 118 publications
(137 reference statements)
1
51
0
3
Order By: Relevance
“…In the United States, an estimated 65% of women diagnosed with mental illness are mothers (Seeman 2002), resulting in a large population of offspring at greater risks for later development of mental disorders/problems. Maternal mental health disorders represent a significant risk for disruption of normal brain development, due to known influences of maternal genetic factors on fetal brain growth (Satyanarayana and others 2011). However, intrauterine (e.g., disrupted hormone release) and postnatal environmental factors (e.g., poorer care giving and lower socioeconomic status) related to mental illness are also likely to contribute to the consequences, either independently or through interactions with genetic factors (Rice and Thapar 2010).…”
Section: Alterations Of Normative Functional Connectivity Developmentmentioning
confidence: 99%
“…In the United States, an estimated 65% of women diagnosed with mental illness are mothers (Seeman 2002), resulting in a large population of offspring at greater risks for later development of mental disorders/problems. Maternal mental health disorders represent a significant risk for disruption of normal brain development, due to known influences of maternal genetic factors on fetal brain growth (Satyanarayana and others 2011). However, intrauterine (e.g., disrupted hormone release) and postnatal environmental factors (e.g., poorer care giving and lower socioeconomic status) related to mental illness are also likely to contribute to the consequences, either independently or through interactions with genetic factors (Rice and Thapar 2010).…”
Section: Alterations Of Normative Functional Connectivity Developmentmentioning
confidence: 99%
“…Mental health during pregnancy (e.g., stress, anxiety, pregnancy-related anxiety, and depression) can influence birth outcomes [ 1 ] including preterm birth [ 2 , 3 ] and low birth weight [ 3 ]. Limited studies examining the role of comorbid anxiety and depression in this literature indicate comorbid anxiety and depression may further increase the risk of preterm birth or low birth weight [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of perinatal depression report point prevalence estimates between 6–13% (Gavin et al, 2005) and studies have shown that 16% present with clinically anxious symptoms during the first trimester (Rubertsson et al, 2014); in addition, 84% of women report some form of psychosocial stress during pregnancy (Woods et al, 2010). Depression, anxiety, and stress during pregnancy have been associated with inadequate antenatal care, low birth weight, preterm delivery, small gestational age, placental abruption, self-harm, suicidal-ideation, postpartum depression, and maladaptive emotional and behavioral development of offspring (de Paz et al, 2011; Farias et al, 2013; Graignic-Philippe et al, 2014; Lee et al, 2007; Sanchez et al, 2013; Satyanarayana et al, 2011; Szegda et al, 2014; Wisner et al, 2013). …”
Section: Introductionmentioning
confidence: 99%